2020
DOI: 10.2147/jmdh.s280261
|View full text |Cite
|
Sign up to set email alerts
|

<p>Screening for Bone Mineral Density and Assessment Knowledge Level of Low Peak Bone Risk Factors and Preventive Practices Among Kuwaiti Future Mothers</p>

Abstract: Background Attaining greater peak bone mass (PBM) prior to the onset of bone loss is getting increasing public health attention as healthy strong bones are essential to maintain our life. Females are more susceptible to bone loss. Knowledge and awareness about low peak bone mass and its related risk factors are important contributors to its preventive behavior. Objective To screen apparently healthy young Kuwaiti future mothers for low bone mineral density (BMD) and to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…A Kuwait cross-sectional study found a link between increased coffee consumption and increased BMD in women aged 18 to 35 years. [ 27 ] Three cohort studies from Asia backed with the same finding. [ 22 , 28 , 29 ] Other research, however, contradicted this finding.…”
Section: Discussionmentioning
confidence: 83%
“…A Kuwait cross-sectional study found a link between increased coffee consumption and increased BMD in women aged 18 to 35 years. [ 27 ] Three cohort studies from Asia backed with the same finding. [ 22 , 28 , 29 ] Other research, however, contradicted this finding.…”
Section: Discussionmentioning
confidence: 83%
“…Adolescence is a critical period for bone mineral accrual, as 40%–60% of adult PBM is accrued during the adolescent years. 8 It is estimated that a 10% increase in the PBM of children and adolescents can reduce the risk of an osteoporotic fracture during adulthood by 50%. 9 In women, the rate of bone accrual peaks in early adolescence (11–14 years old), though bones slowly continue to build in the years immediately following, until PBM is achieved in young adulthood (25–35 years old).…”
Section: Recommendationsmentioning
confidence: 99%